The EXPORT COMPETITIVENESS OF INDONESIAN SPICES TO EUROPEAN UNION-15 - Fadhlan Zuhdi; Lola Rahmadona; Achmad S Maulana (Agric, 2021)
The spice commodity has long been a mainstay of Indonesian exports to the world. Therefore, export of spice commodities needs to be maintained and increased in value in order to balance Indonesia’s trade balance. The potential of the European Union 15 as a large export market for Indonesian spices, so the export of spice commodities must be increased. The current worsening situation (the Sino-United States trade war) has increased the urgency of Indonesia’s exports to other countries. Specifically, this study aims to see the comparative development of Indonesian spice exports to the European Union 15. Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA) and Trade Balance Index (TBI) are used to determine the position of export competitiveness of spices in the European Union 15. The results showed that the RCA value for nutmeg, pepper and cloves > 1 so that the commodity is a competitive spice commodity and is in the maturity stage because it has a TBI> 0.8. Ginger has no competitiveness and is still in the export growth stage. Based on the RSCA, the variations in the competitiveness of the spices of nutmeg, pepper, and cloves during the period 2008 - 2018 have a value of> 0 which means that it has comparative competitiveness, while for ginger the value is <0 so that ginger does not have comparative competitiveness. Efforts that can be taken to further increase export competitiveness in the global market are by developing production and productivity so that they can export to other potential markets such as the Americas and Asia.